The Patio de Machuca in the Alhambra: Documentation of the entrance area to the Nasrid Palace - Arnold, Felix (Madrider Mitteilungen, 2024)
Among the lesser-known areas of the Alhambra are two courtyards which at one time had formed the public access to the Nasrid palace. The so-called Patio de Machuca and the adjoining Patio de la Madraza de los Príncipes were excavated by Modesto Cendoya Busquets in 1915–1923 and restored by Leopoldo Torres Balbás in 1924–1931. Ángel C. López López and Antonio Orihuela Uzal convincingly identified the building as the inner and outer mašwar of Muḥammad V as described by Ibn al-Ḫaṭīb in 1362. The present paper presents the results of a documentation of the remains preserved today. Among the results are indications of previous building phases, as well as construction details. Based on the available information, suggestions of the original appearance of the courtyards are presented, as well as their function within the public audiences of the Nasrid sultan, especially in the context of legal proceedings.